Analysis of Moral Messages in The Film 'Jumbo' Through Roland Barthes' Semiotics - Shendy Aulia Yusuf; Khaerudin Imawan (Greenation International Journal of Tourism and Management, 2026)
The film 'Jumbo' is a 2025 animated film by Ryan Adriandhy produced by Visinema Pictures which tells the story of a friendship adventure containing moral messages and values relevant to everyday life. The film 'Jumbo' shows conflicts related to social conditions or realities that occur in everyday life. The storyline focuses on the emotional journey of the characters. It is studied using Roland Barthes' semiotic approach with three layers of meaning systems, namely denotative, connotative, and myth. The purpose of this study is to determine the moral message through visual signs, characters, or scenes shown in the film and its relevance to social reality. Through qualitative research methods involving observations on the film 'Jumbo' and interviews with film audiences ranging from 18-25 years old. The results of the study show communication values through conflicts that occur between the characters, especially in the aspect of empathy, and the ability to understand each other's feelings. The moral message is also conveyed to be able to appreciate every difference and emphasize the importance of awareness and control of emotions in social relations in society.